2010
DOI: 10.1111/j.1749-818x.2010.00259.x
|View full text |Cite
|
Sign up to set email alerts
|

Issues in the Analysis of Chinese Tone

Abstract: Chinese tone has played an important role in the development of phonological theory from distinctive features and autosegmental phonology to Optimality Theory and its various adaptations. This article reviews some past and current issues in the analysis of Chinese tone and points out how the development of theoretical phonology has shaped the highs and lows of this research enterprise. To fruitfully proceed into the future, I plead to phonologists working in this area to cultivate a new respect for empirical d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 49 publications
(64 reference statements)
1
17
0
Order By: Relevance
“…Our tone sandhi results also echo the sentiment in Zhang [2010] about the prevalence of variations and exceptions in Chinese tone sandhi patterns. Due to the influence of the dominant dialect SC, the increasingly close contacts among different dialects of Chinese, and the differences between literary and colloquial pronunciations in many Chinese dialects, variations and exceptions are par for the course for tone sandhi as well as many other phonological patterns in Chinese.…”
Section: Disyllables -Tone Sandhisupporting
confidence: 66%
See 2 more Smart Citations
“…Our tone sandhi results also echo the sentiment in Zhang [2010] about the prevalence of variations and exceptions in Chinese tone sandhi patterns. Due to the influence of the dominant dialect SC, the increasingly close contacts among different dialects of Chinese, and the differences between literary and colloquial pronunciations in many Chinese dialects, variations and exceptions are par for the course for tone sandhi as well as many other phonological patterns in Chinese.…”
Section: Disyllables -Tone Sandhisupporting
confidence: 66%
“…Our acoustic study on tonal realizations of Tianjin highlights the value of detailed acoustic studies to our understanding of tone patterns, a point also made in Zhang [2010]. The phonetic nature of tones in the inventory of Tianjin has been a contentious issue from the get-go and different researchers have made different assumptions about their representations, often based on impressionistic transcriptions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mandarin has four lexical contour tones, which are phonologically distinctive: for example, shou 1 means "collect", shou 2 means "ripe", shou 3 "hand", and shou 4 "receive" (Zhang, 2010). 1 Chen and colleagues (2002;see also O'Seaghdha et al, 2010;Zhang, 2008) have shown that tone is relevant for implicit priming.…”
Section: Mandarin Lexical Tonementioning
confidence: 99%
“…Mandarin has four lexical contour tones, which are phonologically distinctive: for example, shou 1 means “collect”, shou 2 means “ripe”, shou 3 “hand”, and shou 4 “receive” (Zhang, 2010). 1 Chen and colleagues (2002; see also O’Seaghdha et al, 2010; Zhang, 2008) have shown that tone is relevant for implicit priming.…”
Section: Introductionmentioning
confidence: 99%